Corporate Social Responsibility, Stock Returns and Risk: Evidence from Polish Stock Market - Pawel PERZ (Communications of International Proceedings, 2021)
The impact of activities undertaken by public companies in the field of CSR on stock performance is the subject of numerous theoretical and empirical analyzes. At the same time, empirical studies document both the positive, neutral and negative impact of CSR activities on the financial performance and stock prices. The aim of the article is to compare stock returns of socially responsible companies, included in social responsible firms index created by Warsaw Stok Exchange: ‘RESPECT index’ with other firms. The analysis covered the period from 2009 to 2019. Research shows that average yearly rate of return on the CSR stocks (included in RESPECT index) was 5,19%, compared with 0,36% for stocks included in WIG20 index, and 4,55% for all stock listed in main market. The results support the thesis that CSR activities have a positive impact on the stock prices. But at the same time CSR stock returns are more volatile than other stocks returns so the Sharpe ratio for them are almost the same as for all stocks in the market (0,33 vs 0,32).
Keywords: Corporate Social Responsibility; stock returns; risk; Warsaw Stock Exchange.